Factors behind job preferences of Peruvian medical, nursing and midwifery students: a qualitative study focused on rural deployment - Huicho, Luis (2015)
Background: Deployment of health workforce in rural areas is critical to reach universal health coverage. Students’ perceptions towards practice in rural areas likely influence their later choice of a rural post. We aimed at exploring perceptions of students from health professions about career choice, job expectations, motivations and potential incentives to work in a rural area. Methods: In-depth interviews and focus groups were conducted among medical, nursing and midwifery students from universities of two Peruvian cities (Ica and Ayacucho). Themes for assessment and analysis included career choice, job expectations, motivations and incentives, according to a background theory a priori built for the study purpose. Results: Preference for urban jobs was already established at this undergraduate level. Solidarity, better income expectations, professional and personal recognition, early life experience and family models influenced career choice. Students also expressed altruism, willingness to choose a rural job after graduation and potential responsiveness to incentives for practising in rural areas, which emerged more frequent from the discourse of nursing and midwifery students and from all students of rural origin. Medical students expressed expectations to work in large urban hospitals offering higher salaries. They showed higher personal, professional and family welfare expectations. Participants consistently favoured both financial and non-financial incentives. Conclusions: Nursing and midwifery students showed a higher disposition to work in rural areas than medical doctors, which was more evident in students of rural origin. Our results may be useful to improve targeting and selection of undergraduate students, to stimulate the inclination of students to choose a rural job upon graduation and to reorient school programmes towards the production of socially committed health professionals. Policymakers may also consider using our results when planning and implementing interventions to improve rural deployment of health professionals.